REPRESENTATION OF VILLAGE COURTYARD LIFE IN WORLD GENRE PAINTING: SOCIAL AND CULTURAL INSIGHTS” - Alimova Dinara Namozovna (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2026)
This article explores the portrayal of village courtyard life in world genre painting. It focuses on how artists depict daily activities, family interactions, labor, and leisure, emphasizing the relationship between humans and their natural environment. The study examines works from European and Russian painters to highlight how these paintings serve both aesthetic and cultural purposes. Village courtyard scenes preserve social norms, historical context, and human-environment interactions, offering valuable insight into rural life across different periods and regions.